The Role of Non-Governmental Organizations in the Localization of Gender-Based Violence Standards in South Africa - Syakira, Hana; Afriani Sinulingga, Anita; Elian Nasir, Putiviola (Palito, 2025)
This research aims to show how the interaction between the actors is in the process of ending gender-based violence norms brought in by international norms entrepreneurs such as UN Women, UNICEF, and UNFPA is then adapted to local practices by local actors in South Africa. South Africa is one of the highest gender-based violence in the world. The increasing number of cases have prompted local actors such as Sonke Gender Justice, the South African Youth Gender Action Plan and the Foundation for Human Rights who are engaged in the fulfilment of gender and human rights to contribute to the prevention of gender-based violence. This research used the concept of norms localization by Amitav Acharya. The method used in this study is a qualitative method with a type of descriptive analysis research from secondary data. This research has shown the interaction between international organizations, state, and local NGOs, particularly at the domestic level in the process of adjusting the norm of ending GBV. This research has also shown how interactions between these actors have successfully localized the norms characterized by institutional changes in the form of the issuance of the National Strategic Plan on Gender-Based Violence and Femicide by the South African government.